An Analytical Study on the Application of Justice Theory in the Perspective of Legal Philosophy: A Case Study of the Aggravated Assault on David Ozora - Maghfiroh, Laily; Hidayat, Muhammad Rahmadzani; Salsabila, Syana Mifta; Putri, Syifadilla Subagyo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Justice is the primary goal of law and serves as the basis for every law enforcement process in Indonesia. The case of the serious assault on Cristalino David Ozora by Mario Dandy Satriyo reflects a test of the value of justice amidst social and power inequality. This study uses a normative method with a literature review to analyze the concept of justice theory from the perspective of legal philosophy, particularly according to Aristotle, John Rawls, and Gustav Radbruch. The results show that the application of justice theory in this case emphasizes the importance of equality before the law and the moral responsibility of the perpetrator. The court's decision to sentence the victim to 12 years in prison and require restitution to the victim reflects the application of commutative and distributive justice. This also shows that law enforcement in Indonesia must balance legal certainty, moral values, and humanity as the basis for achieving substantive justice.